Advanced power cycles for concentrated solar power. (August 2017) - Stein, W.H.; Buck, R.
Highlights: Advanced power cycles under consideration for the next generation of CSP are reviewed. Higher efficiency, and thus higher temperature cycles, are generally the most attractive. Flexibility in both operation and capacity, plus dispatchability, are also critical features. Supercritical CO2 closed Brayton cycles and air turbine based cycles are reviewed in detail. Abstract: This paper provides a review of advanced power cycles under consideration for CSP. As variable renewables make rapid commercial progress, CSP with thermal energy storage is in an excellent position to provide low cost stability and reliability to the grid, however higher efficiency and lower costs are critical. Steam turbines provide a robust commercial option for today but more advanced power cycles offering greater agility and flexibility are needed. Supercritical steam turbines are attractive at large scale but presently commercial products are too large for today's solar towers, unless multiple towers with an aggregating heat transfer fluid is used. CSP/PV hybrids combine benefits of PV's and low cost thermal storage. Supercritical CO2 closed loop Brayton cycles are early in their development but promise high efficiency at reasonable temperatures across a range of capacities, with the prospect of significantly lowering costs. The next few years building knowledge on materials and components cost and performance along with demonstration is crucial. Gas turbine combined cycles driven by CSP are one of the highest efficiency options available, though other bottoming and topping cycle configurations should be progressed also. Again, component demonstration at the required high temperatures is critical.